2014
DOI: 10.1111/1346-8138.12514
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the cause of severe skin infection by Fournier transform infrared spectroscopy: A case of Fournier's gangrene caused by fish bone

Abstract: Fournier's gangrene (FG) is an infrequent but highly lethal infection. Here we report a 74-year-old man who presented with genital swelling and severe malaise. Based on the physical and imaging examination results, the diagnosis of FG was confirmed. Intraoperative findings showed dirty necrosis of soft tissue, and a splinter-shaped foreign body was found in the perirectal region. The foreign body was thought to be the cause of the condition, and it was analyzed using Fourier transform infrared spectroscopy. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The process for identifying and selecting the relevant studies according to the inclusion and exclusion criteria is shown in Figure 1. After screening the titles or abstracts and retrieving the full texts, 20 studies, including 15 Chinese studies (10-24) and 5 English-language studies (7,(25)(26)(27)(28), published between 2000 and 2020 met the inclusion criteria, and a total of 35 male patients were analyzed for this systematic review, including 20 Chinese patients with an age range of 70.70±6.76 years, and 15 non-Chinese patients with and age range of 70.83±7.14 years. The full text of all the included studies was available.…”
Section: Study Selection and Patient's Characteristicsmentioning
confidence: 99%
“…The process for identifying and selecting the relevant studies according to the inclusion and exclusion criteria is shown in Figure 1. After screening the titles or abstracts and retrieving the full texts, 20 studies, including 15 Chinese studies (10-24) and 5 English-language studies (7,(25)(26)(27)(28), published between 2000 and 2020 met the inclusion criteria, and a total of 35 male patients were analyzed for this systematic review, including 20 Chinese patients with an age range of 70.70±6.76 years, and 15 non-Chinese patients with and age range of 70.83±7.14 years. The full text of all the included studies was available.…”
Section: Study Selection and Patient's Characteristicsmentioning
confidence: 99%
“…14 Ingested fish bone may perforate the rectosigmoid colon and cause anorectal infections that can develop into Fournier's gangrene. 14 Risk factors for Fournier's gangrene are diabetes mellitus, alcohol abuse, and liver cirrhosis. 15 Patients with Fournier's gangrene can have various symptoms, such as fever, pain and swelling in the genital or anal area, an unpleasant odor from the affected skin tissue, and a crackling sound when touching the affected area.…”
Section: Fournier's Gangrenementioning
confidence: 99%
“…Only about 10 cases have been reported, and almost all case reports of Fournier’s gangrene due to fish bone were from Japan. 14 Ingested fish bone may perforate the rectosigmoid colon and cause anorectal infections that can develop into Fournier’s gangrene. 14 Risk factors for Fournier’s gangrene are diabetes mellitus, alcohol abuse, and liver cirrhosis.…”
Section: Rare and Critical Complicationsmentioning
confidence: 99%